Prospective Teachers’ Perceptions of Using Information and Communication Technologies in Biology Education: Insights from Some Colleges of Teacher Education in Ethiopia - Adane Sifer Besir; Getachew Sime Feyissa; Mulugeta Yayeh Worku; Girma Tilahun Yimer (Science Education International)
The use of information and communication technologies (ICTs) for teaching and learning is widely acknowledged. However, there is limited research focusing on prospective teachers’ (PTs) perceptions regarding its usage within specific subject areas, notably biology. This study is intended to explore PTs perceptions of using ICT in biology. Mixed-method approaches were used. Questionnaires and semi-structured interviews were used to collect data. The study subjects, 142 PTs, were selected using purposeful and stratified random sampling techniques. The result shows PTs had a positive perception of ICTs, with significant differences based on gender and ICT experience (p < 0.05). As a result, those with less ICT experience, along with females, tend to have a lower perception of ICT use, emphasizing the need for targeted support to bridge these gaps and empower them in ICT integration. The correlation analysis showed ICT usage is positively linked to PTs’ perceived usefulness of ICT (r = 0.48) and their perceived ICT abilities (r = 0.62). Regression analysis revealed that 40.8% of PTs’ ICT usage in biology is predicted by these factors, indicating a strong relationship. The study offers valuable insights for teacher education programs, emphasizing the need to enhance PTs’ ICT skills and self-efficacy, which is critical for advancing educational goals in developing nations such as Ethiopia.